Beyond geometrical overlap: a Dosimetrical Evaluation of automated volumes Adaptation (DEA) in head and neck replanning. (September 2017) - Mattiucci, Gian Carlo; Boldrini, Luca; Placidi, Lorenzo; Azario, Luigi; Dinapoli, Nicola; Chiloiro, Giuditta; Pasini, Danilo; Piccari, Danila; Gambacorta, Maria Antonietta; Balducci, Mario; Mantini, Giovanna; Valentini, Vincenzo
Highlights: Replanning handles anatomical and dosimetric modifications during treatment. Replanning needs segmentation of the new simulation CT: this is time consuming. Automated adaptation of replanning imaging requires careful manual correction. New similarity indices are needed for more accurate dose coverage evaluations. Abstract: Introduction: Automated target volumes adaptation could be useful in H&N replanning, but its dosimetric impact has not been analyzed. Primary aim of this investigation is dose coverage assessment in fully automated and edited PTV adaptation settings, compared to manual benchmark. Materials and methods: Ten IMRT patients were selected and replanning CTs were acquired. A deformable registration with PTV adaptation was performed defining PTVA. PTV B was obtained through manual editing and a benchmark PTV C was manually segmented by a delineation team. The Dice Similarity Index (DSI) and the mean Hausdorff Distance (mHD) were calculated between PTV A and PTV C, and between PTV B and PTV C. One IMRT plan was realized for each PTV: the plans optimized on PTV A and PTV B were proposed on PTV C to evaluate their dosimetric reliability compared to the benchmark plan in terms of PTV V95% dose coverage. Results: The comparisons between PTV A with PTV C and PTV B with PTV C showed that the better DSI (high) and mHD values (low) are, the smaller difference when compared to PTV C V95% is described. Evaluating plan A and B, PTV C V95% reduced by 6.1 ± 3.0% and by 4.1 ± 2.3% respectively when compared to plan C PTV C V95%. PTV B reaches acceptable dose coverage values (PTV V95% >95%) when DSI is >0.91 and a mHD < 0.17 mm and it has better results when compared to PTV A in 70%. Discussion: The results show a correlation between the DSI-mHD and the PTV V95% variation, in the comparisons PTV A and PTV B vs PTV C. Furthermore, we observed that PTV V95% coverage is higher in PTV B than in PTV A: the use of automated propagation may not be definitive and requires manual correction.